2014
DOI: 10.3168/jds.2014-8226
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the feeding behavior of dairy cows through live yeast supplementation

Abstract: The objective of this study was to determine if the feeding behavior of dairy cows is modified through live yeast supplementation. Twelve lactating Holstein dairy cows (2 primiparous and 10 multiparous) were individually exposed, in a replicated crossover design, to each of 2 treatment diets (over 35-d periods): (1) a control TMR and (2) a control TMR plus 1 × 10(10) cfu/head per day of live yeast (Saccharomyces cerevisiae CNCM I-1077; Levucell SC20; Lallemand Animal Nutrition, Montreal, QC, Canada). Milk prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 39 publications
4
36
0
Order By: Relevance
“…However, the relative abundance of Prevotella was not affected (P = 0.13) by the interaction between dietary treatment and time relative to calving (with the relative abundance of Prevotella being numerically lower in LY than in control cows), which would indicate that rumen pH between control and LY cows probably did not substantially differ after calving. However, several studies have reported improvements in rumen pH when supplementing lactating cows with LY (Bach et al, 2007;Thrune et al, 2009;DeVries and Chevaux, 2014). The hypothetical lack of differences in rumen pH (as potentially indicated that the relative abundance of Prevotella) could be found in the important differences in DMI, which was much greater in LY than in control cows.…”
Section: Rumen Microbiotamentioning
confidence: 99%
“…However, the relative abundance of Prevotella was not affected (P = 0.13) by the interaction between dietary treatment and time relative to calving (with the relative abundance of Prevotella being numerically lower in LY than in control cows), which would indicate that rumen pH between control and LY cows probably did not substantially differ after calving. However, several studies have reported improvements in rumen pH when supplementing lactating cows with LY (Bach et al, 2007;Thrune et al, 2009;DeVries and Chevaux, 2014). The hypothetical lack of differences in rumen pH (as potentially indicated that the relative abundance of Prevotella) could be found in the important differences in DMI, which was much greater in LY than in control cows.…”
Section: Rumen Microbiotamentioning
confidence: 99%
“…A better fibre digestibility may also been linked to changes in feed intake pattern which have been measured in the presence of live yeasts (Bach et al . ; Devries and Chevaux ). More generally, greater fibre digestion benefits milk production (Oba and Allen ).…”
Section: Introductionmentioning
confidence: 97%
“…The positive effects on fibre digestion can be partly responsible for the increase in dry matter intake (DMI) which can be observed with yeast supplementation (Marden et al 2008;Desnoyers et al 2009), DMI being correlated with neutral detergent fibre (NDF) digestibility (Oba and Allen 1999). A better fibre digestibility may also been linked to changes in feed intake pattern which have been measured in the presence of live yeasts (Bach et al 2007;Devries and Chevaux 2014). More generally, greater fibre digestion benefits milk production (Oba and Allen 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Saccharomyces cerevisiae is typically fed to dairy cattle either as a live yeast (LY) or as a yeast culture (YC) containing live and dead cells and the products of fermentation, or a combination of both, with the aim of altering ruminal fermentation in an attempt to improve nutrient digestion and N utilization, and to stabilize ruminal pH, reducing the risk of ruminal acidosis, and improve animal performance (Desnoyers et al, 2009). Experiments have documented that provision of LY or YC has potential to modify dairy cow feeding behavior patterns (Bach et al, 2007;DeVries and Chevaux, 2014;Dias et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%